Estudo da flotação de minério silicatado de zinco sem a etapa de deslamagem - Lemyr Martins (2007)
The world measured reserves of zinc reached, in 2005, 462 x 106 t of the metal, the Brazilian reserves representing 1.2% of the world reserves. Approximately 82.9% of the Brazilian reserves are located in Vazante and Paracatu, in the northwest of Minas Gerais state. The ore from the Vazante deposit is oxidized. The apparent consumption of zinc concentrate in Brazil reached 592 x 103 t in 2005. The increase in sales of zinc in the coming years is estimated in 4% per year. Aiming at increasing the grade and recovery of the zinc concentrate produced in Vazante, the investigation included mineralogical characterization, dispersion studies, bench scale and pilot scale flotation experiments,and an industrial flotation test. The objective was to verify the flotation behavior of the silicate zinc ore (calamine type) in the presence of slimes, with the aid of dispersing agents. The characterization studies identified as major minerals hemimorphite (calamine), quartz, and dolomite. The dispersion tests showed that the enhanced dispersion of the particles in the pulp in the absence of reagents is observed in the pH range between 8.5 and 12.0. The statistical tool of complete factorial design at two levels replicated once was used for planning the bench scale flotation experiments. The studies showed, and were confirmed at pilot plant scale, that the dosages of sodium sulfide and combination of polymeric dispersant and sodium silicate at the higher level favored a higher metallurgical recovery. For addition levels of 6800 g/t of sodiumsulfide and 6992 g/t of dispersing agent combined with sodium silicate, 38.40% zinc grade in the final concentrate was achieved at an average metallurgical recovery of 72.40%. The industrial test without previous desliming confirmed the pilot scale results, leading to zinc recovery of 76.09%, at zinc grade in the concentrate of 37.30%.